Taming Global Finance in an Age of Capital? Wage-Setting Institutions' Mitigating Effects on Housing Bubbles - Alison Johnston; Aidan Regan (London School of Economics and Political Science (LSE), European Institute, 2015)
Analyses in international political economy (IPE) identify interest rate convergence, magnified in the process of European monetary integration, and financial market liberalization as causal factors behind the rise of house prices. Despite these common credit supply shocks, developed economies experienced heterogeneous trends in housing inflation throughout the 1990s and 2000s. Turning towards demand determinants of housing prices, we focus on whether wage-setting institutions blunt financial liberalization's impact on housing inflation via their restraining effect on incomes. Employing both a panel regression analysis and a structured comparison of housing developments in Ireland and the Netherlands, we uncover two findings. First, income growth is a more important predictor of housing bubbles across OECD economies than financial variables (although income's impact on house prices is severely mitigated for the United States). Second, countries with coordinated labor market institutions that grant political coalitions in the export sector veto powers over non-tradable sector interests, realize more restrained income growth and, in turn, are less prone to housing bubbles.
Keywords: 330; housing prices; wage setting institutions; financial liberalization; Ireland; the Netherlands